2015
DOI: 10.5650/jos.ess15055
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Biological Activities of <i>Allium roseum</i> L. var. grandiflorum Briq. Essential Oil

Abstract: International audienceAllium roseum L. (Alliaceae) endemic mediterranean specie was represented in the North Africa by 12 different taxa. In the present study, chemical composition, antiproliferative, antioxidant and antimicrobial activities of the essential oil extracted from A. roseum var. grandiflorum Briq. bulbs collected in the North of Tunisia were investigated. Chemical characterization has shown methyl methanethiosulfinate as major sulphurous compounds. A. roseum bulbs essential oil provides interestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Sulfur-containing compounds have the ability to inhibit the activity of the xanthine-xanthine oxidase system and attenuate ROS-induced lipids and proteins peroxidation [22]. Garlic organosulfur compounds also attenuate lipids peroxidation by inhibition of xanthine-xanthine oxidase-induced ROS generation [23]. In addition, during biotransformation processes, thiosulfonates are able to transform into other sulfur-containing compounds and thiols, which can be further used as a material for the synthesis of GSH molecules [24].…”
Section: Resultsmentioning
confidence: 99%
“…Sulfur-containing compounds have the ability to inhibit the activity of the xanthine-xanthine oxidase system and attenuate ROS-induced lipids and proteins peroxidation [22]. Garlic organosulfur compounds also attenuate lipids peroxidation by inhibition of xanthine-xanthine oxidase-induced ROS generation [23]. In addition, during biotransformation processes, thiosulfonates are able to transform into other sulfur-containing compounds and thiols, which can be further used as a material for the synthesis of GSH molecules [24].…”
Section: Resultsmentioning
confidence: 99%
“…EOs from Heracleum pyrenaicum subsp. orsinii , Pistacia vera L., Myrcia ovata Cambessedes , Thymus bovei , Minthostachys verticillata , Allium roseum , Petroselinum crispum , Satureja bachtiarica Bunge, Ocimum suave , Jatropha gossypifolia L., and Juniperus rigida have been shown to exert antibacterial and anti-yeast effects [34,37,41,43,47,48,51,64,67,68,69]. One of the proposed mechanisms for those effects is the irreversible damage of the bacteria cell wall and membrane, which leads to not only a leakage of proteins but also of DNA and RNA molecules [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, in human colonic adenocarcinoma cancer cell lines (HT29-D4 and Caco-2 cell), Allium roseum L. EO has a growth-inhibitory effect in a dose-dependent manner, without being cytotoxic. This effect has been attributed to the presence of sulfurous compounds as the major constituents of this EO [68]. Conversely, Cirsium japonicum DC EOs could promote cell proliferation in the human pulmonary adenocarcinoma A549 cell line [92].…”
Section: Discussionmentioning
confidence: 99%
“…Pinus pinaster needles exhibited a low yield of the essential oils when compared with Aleppo pine needles growing in Algeria with a yield of 0.52%. 14 The chemical composition of the essential oil of needles was investigated using GC-FID and GC-MS apparatus. The chromatograms of P. pinaster of two varieties showed that the essential oils were a mixture of numerous compounds; some of them were present in trace amounts.…”
Section: The Chemical Composition Of Essential Oilsmentioning
confidence: 99%